The importance of psychology in controlling the behavior of emotions in traffic in the light of Skinner's theory and other contributions - Lira, Louise Lorena Lopes; Lira, Luiz Alberto Rocha de (Seven Editora, 2024)
The present study aims to analyze human behavior in traffic influenced by subjective emotions, considering the Brazilian case under analysis, as well as its circumstantial aspects. The country has in its statistics the highest number of deaths in traffic, with most caused by drunkenness, distractions and aggressiveness. Such reasons can also be caused by consequences of pre-conceived emotional states in other areas of life, be it professional, romantic, family or social. In this context, it is important to report on the role of psychology and the professional psychologist and the imminent possibility of their preventive contribution in a positive way in the prevention of accidents, analyzing the human being in his life trajectory and evaluating the superlative factors that may be influencing, and in some way, indicating reckless actions in traffic. In this way, a specialized diagnosis can help drivers to manage, drive and understand their feelings in a more balanced way, taking advantage of elements to reflect on their condition as a driver and their relationships in the social environment, through the act of driving in a context population in which there are established rules and norms. In another aspect, which adds relevance to the general objective and is important to support the theoretical foundation of the proposed study, it was to bring to this discussion, in the field of behavioral psychology, one of the main interventions in the works of Burrhus Frederic Skinner, one of the most important aspects of psychology in the behavioral area that dominated innovative practices and ideas in schools and clinics. Such interventions are remarkable in the sense of jointly explaining the repercussions of positive projects by psychologists so that institutions can further evaluate and value the aspects of mental health, not only as a restorative action by the professional, but also as a preventive action.Therefore, from methodological aspects, this is a bibliographic and qualitative research, in which articles, reports and books were used as data collection tools.The study will reveal that emotional reactions, whether primary such as: fear, disgust, surprise anger, happiness and sadness or secondary such as stress, jealousy, pride, guilt, shame among others, can directly influence traffic accidents, but there are ways of control. DOI:https://doi.org/10.56238/sevened2024.001-020